THE EFFORTS TO FULFILL RESTITUTION FOR VICTIMS OF RACIAL AND ETHNIC DISCRIMINATION CRIMES IN INDONESIA - Kurniawan, Yandi; Subhandi Bakhtiar, Handar (Kertha Semaya : Journal Ilmu Hukum; Vol 12 No 12 (2024), 2025)
Tujuan dari penelitian ini adalah untuk mengkaji terkait pemberian restitusi kepada setiap warga negara Indonesia yang terdampak akibat tindak pidana diskriminasi ras dan etnis, karena hal dinilai sangat penting bagi pemerintah yang mana menghormati nilai-nilai perlindungan hukum. Penelitian ini adalah penelitian yuridis normatif yang meneliti terkait norma hukum positif yang menempel pada peraturan perundang-undangan yang berhubungan dengan distribusi hak restitusi bagi korban tindak pidana ras dan etnis di Indonesia. Hasilnya membuktikan bahwa restitusi kepada korban tindak pidana diskriminasi ras dan etnis berdasarkan peraturan perundang-undangan dikerjakan oleh Lembaga Perlindungan Saksi dan Korban dan Kejaksaan. Demi memperoleh restitusi wajib diajukan oleh korban kepada lembaga tersebut, maka lembaga ini hanya reaktif yang artinya akan bereaksi sesudah adanya permohonan dari pihak korban. The purpose of this research is to examine the provision of restitution to every Indonesian citizen affected by criminal acts of racial and ethnic discrimination, because it is considered very important for the government which respects the values of legal protection. This research is a normative juridical research that examines positive legal norms attached to laws and regulations related to the distribution of restitution rights for sufferers of racial and ethnic crimes in Indonesia. The results prove that restitution to victims of racial and ethnic discrimination crimes based on legislation is carried out by the Witness and sufferers Protection Agency Prosecutor. In order to obtain restitution, it must be submitted by the victim to the institution, so this institution is only reactive, which means that it will react after a request from the victim.